Aspects of biology and exploitation of Sepia aculeata Orbigny from Mangalore area, Karnataka - Rao, G Syda (Indian Journal of Fisheries, 2011)
Sepia aculeata is the most important component of cuttlefish landings at Mangalore. The major spawning season is October to March. It attains first maturity at a dorsal mantle length of 86 mm. Females are dominant particularly beyond 150 mm length. The fecundity ranges from 206 to 1,568 ova. Relative fecundity is the highest at 94 mm length and progressively declines with increase in length. Significant difference is observed in lengthweight relationship between immature and mature cuttlefish in either sex. The fluctuations of gonad, nidamental gland and hepatic indices are correlated to the maturity and spawning habits of S. aculeata. The growth parameters are estimated by Gulland and Holt plot as L_= 231 mm K = 0.0041/day and t = -41days. This species reaches a length of 181 mm at the end of one year.